An econometric evaluation of bank recapitalization programs with bank- and loan-level data - Nakashima, Kiyotaka (Journal of Banking & Finance, 2016)
Public capital injections into the banking system are a comprehensive policy program aimed at reducing the financial risks faced by capital-injected banks, thereby stimulating their lending and profitability. This paper evaluates empirically Japan’s two large-scale capital injections in 1998 and 1999. We begin by extracting the treatment effects of the public injections from bank-level panel data. Using a difference-in-difference estimator in two-way fixed-effects regression models, we find that the public injections significantly reduced the financial risks faced by the capital-injected banks but did not stimulate their lending or profitability. Next, we investigate what factors impeded bank lending after the public injections using a matched sample of Japanese banks and their borrowers. By employing three-way fixed-effects regression models corresponding to the matched sample, we provide evidence that the deterioration of borrowers’ creditworthiness inhibited not only the injected banks but also the noninjected banks from lending more.